Statíny do pitnej vody? Riziko vedľajších účinkov a nízkych hladín cholesterolu - Ginter, Emil; Kajaba, Igo; Sauša, Marián (Casopis lekaru ceskych, 2012)
After the discovery of antibiotics, statins, the inhibitors of cholesterol synthesis have been the best-selling prescription drug in the world. These drugs have well documented benefits for cardiovascular disease in many groups of patients at moderate and high cardiovascular risk. US Health authorities are currently pushing for anti-cholesterol drugs to be added to the public water supply. Statins in-depth studies have shown that they can actually have a detrimental effect on the health of people without high cholesterol or heart disorders. Statins should be prescribed only to those patients with heart disease, or who have suffered the condition in the past. Researchers warn that unless a patient is at high risk of the heart attack or stroke, statins may cause more harm than good.
Keywords: infarkt myokardu; Hydroxymethylglutaryl-CoA Reductase Inhibitors; zásobování vodou; Cholesterol; statiny; cévní mozková příhoda; cholesterol; Stroke; lidé; Water Supply; Humans; Myocardial Infarction